Parkinsonism complicating acute organophosphate insecticide poisoning - Hashim, Hasnur Zaman; Wan Musa, Wan Rosmaiza; Chai, Soon Ngiu; Wan Yahya, Wan Nafisah; Hui, Jan Tan; Ibrahim, Norlinah (Academy of Medicine, Singapore, 2011)
Organophosphate insecticides have a triphasic effect on the central nervous system, namely acute cholinergic crisis, intermediate syndrome and delayed polyneuropathy. Although acute organophosphate poisoning is relatively common, case reports describing parkinsonism as a neurological complication following an acute intoxication are limited. 1 We report a case of parkinsonism noted on day 24 of admission following an acute severe organophosphate poisoning which was successfully treated with benzhexol and levodopa. Previously, response to levodopa was reported to be poor in 3 patients studied by Bhatt et al 1whereas amantidine, dopamine agonist and bipiriden have been shown to be helpful. 2To the best of our knowledge, this is the ﬁ rst case of parkinsonism complicating organophosphate poisoning which responded to levodopa and benzhexol therapy.